The Role of Social Media in Influencing Generation Z's Shopee Food Purchase Decisions in Palembang City - Pranata, Riza; Gunarto, Muji; Helmi, Sulaiman (Yayasan Sinergi Kawula Muda, 2025)
This study aims to analyze the influence of social media on the purchasing decisions of Generation Z in the city of Palembang, especially on food delivery services such as Shopee Food. Social media, which has become an integral part of Gen Z's life, plays an important role in shaping consumer purchasing decisions, especially through content that includes promotions, consumer reviews, and influencer recommendations. This study uses a qualitative approach with a case study design, where data is collected through in-depth interviews with Generation Z consumers, Shopee Food business actors, and digital marketing experts. The results of the study show that social media content, such as discount promos, influencer recommendations, and content personalization, has a big influence on purchasing decisions. In addition, the ease of use of the application, menu variety, and service quality are the main supporting factors in choosing Shopee Food services. This research suggests that Shopee Food continues to utilize social media as the main marketing strategy to reach consumers, while adapting their marketing approach to the needs and preferences of consumers in the city of Palembang to maintain competitiveness.